Zastosowanie modelowania GIS w ocenie georóżnorodności = The application of GIS modeling for geodiversity evaluation - Kot, Rafał; Kot, Rafał (Polska Asocjacja Ekologii Krajobrazu, 2014)
Geodiversity is understood as a variation of all abiotic components in geographical environment. Its evaluation in spatial analysis requires construction of a number of maps as well as data analysis. In these works GIS tools and programs are useful. In this study, many different tools were used: reclassification, vectorization, aggregation, intersection, as well as operations on attribute tables, for example field calculator or summarization. Using the possibilities of ArcInfo, ModelBuilder tool built GIS models that significantly improve work on the geodiversity valuing. Constructed models have been tested on the example of slopes. Once digitized, all the contour-lines (isohypses) from the map in a scale of 1:50 000, and the use of tools Raster to Topo, digital elevation model (DEM) with resolution of grid 20 m was made. DEM was the basis for generating digital terrain model (DTM) and maps of slopes. On the basis of these maps slope values were calculated (maximum, minimum, range), as well as number of classes (PR patch richness), number of units (NP number of patches), Shannon’s diversity index (SHDI), Simpson’s diversity index (SIDI) and roughness coefficients (R, Rw). Study area, covering an area of 288 km2, was a fragment of the Polish Lowland west of Toruń.
Bibliogr.
Summ. eng.
244 p. : il. (color.) ; 24 cm
Keywords: geodiversity; primary topographic attributes; Polish Lowland; GIS models